DAMPAK PEMBELAJARAN SAAT PANDEMI DALAM MENSTIMULASI KEMAMPUAN SOSIAL ANAK DI TK NEGERI PEMBINA 01 PANCUNG SOAL PESISIR SELATAN - Selvi Selvi jantrika; Serli Marlina (Pendidikan Guru PAUD, FKIP, Univ Muhammadiyah Tasikmalaya, 2021)
Social development is defined as the ability of children to interact with peers, adults and the wider community. At this time, children’s social abilities cannot be stimulated properly because learning in stimulating children’s social abilities has not been carried out optimally, due to the Covid-19 pandemic virus outbreak, so the learning system is carried out briefly, there are no activities to play, eat together, and line activities – marching is eliminated. This study aims to describe the impact of learning during a pandemic in stimulating children’s social abilities. The method used in this research is descriptive qualitative, and class B teachers are the informants in this study. The result showed that during the pandemic the impact of learning in stimulating children’s social abilities had an ineffective impact due to the short learning process. The development of children’s social abilities has not been optimally stimulated during the pandemic because of limited time for learning.